A segment of the C-terminal half of the G-protein beta 1 subunit specifies its interaction with the gamma 1 subunit. - Katz, A (1995)
The beta and gamma subunits of the heterotrimeric guanine nucleotide binding (G protein) act as a dimer and directly regulate various signal transduction pathways. By using cotransfection assays, we tested the ability of several beta gamma combinations to activate inositol phospholipid-specific phospholipase C (PI-PLC)-beta 2. Our findings indicate that only beta gamma combinations that form dimers will activate PI-PLC-beta 2. Since G beta 1 interacts with G gamma 1, while G beta 2 cannot, chimeras between G beta 1 and G beta 2 were used to identify the regions in beta 1 that determine its specific association with gamma 1. Our evidence demonstrates that a chimera between beta 2 and beta 1 that contains the C-terminal 173 amino acids of beta 1 can interact and activate PI-PLC-beta 2 with gamma 1. Chimeras that contain portions of the beta 1 C-terminal region display a weaker association with gamma 1. Furthermore, the contribution of each of these regions depends on the sequence context of each chimeric protein. However, the segment between residues 210 and 293 of beta 1 consistently plays a critical role in specifying association with gamma 1.